Beyond the drugs: nonpharmacologic strategies to optimize procedural care in children. Issue 1 (February 2016) - Leroy, Piet L.; Costa, Luciane R.; Emmanouil, Dimitris; van Beukering, Alice; Franck, Linda S.
Abstract : Purpose of review: Painful and/or stressful medical procedures mean a substantial burden for sick children. There is good evidence that procedural comfort can be optimized by a comprehensive comfort-directed policy containing the triad of nonpharmacological strategies (NPS) in all cases, timely or preventive procedural analgesia if pain is an issue, and procedural sedation. Recent findings: Based both on well-established theoretical frameworks as well as an increasing body of scientific evidence NPS need to be regarded an inextricable part of procedural comfort care. Summary: Procedural comfort care must always start with a child-friendly, nonthreatening environment in which well-being, confidence, and self-efficacy are optimized and maintained. This requires a reconsideration of the medical spaces where we provide care, reduction of sensory stimulation, normalized professional behavior, optimal logistics, and coordination and comfort-directed and age-appropriate verbal and nonverbal expression by professionals. Next, age-appropriate distraction techniques and/or hypnosis should be readily available. NPS are useful for all types of medical and dental procedures and should always precede and accompany procedural sedation. NPS should be embedded into a family-centered, care-directed policy as it has been shown that family-centered care can lead to safer, more personalized, and effective care, improved healthcare experiences and patient outcomes, and more responsive organizations.